2010
DOI: 10.1103/physrevlett.104.243601
|View full text |Cite
|
Sign up to set email alerts
|

Pump-Induced Dynamical Tunneling in a Deformed Microcavity Laser

Abstract: Pump-induced dynamical tunneling has been observed in free-space resonant optical pumping of a deformed microcavity by employing excitation spectroscopy. A focused-pump beam was injected into the cavity by refraction and then coupled to a high-Q cavity mode via dynamical tunneling. Pump-coupling efficiency as high as 50% and an effective coupling constant responsible for the tunneling were obtained from the observed pumping efficiency with a mode-mode coupling model. DOI: 10.1103/PhysRevLett.104.243601 PACS n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…(11), |a ω | 2 describes the excitation probability by the free-space beam, from which we can deduce that the FWHM (full width at half maximum) of the regular mode is expressed as κ + γ ≡ γ t . It should be noted that γ t remains unchanged when the free-space coupling efficiency changes [27], while in fiber taper coupling the total decay rate will vary.…”
Section: Dynamical Tunneling-assisted Couplingmentioning
confidence: 99%
See 2 more Smart Citations
“…(11), |a ω | 2 describes the excitation probability by the free-space beam, from which we can deduce that the FWHM (full width at half maximum) of the regular mode is expressed as κ + γ ≡ γ t . It should be noted that γ t remains unchanged when the free-space coupling efficiency changes [27], while in fiber taper coupling the total decay rate will vary.…”
Section: Dynamical Tunneling-assisted Couplingmentioning
confidence: 99%
“…It has been demonstrated that WGMs in a specially designed deformed cavity can be directly excited by a freespace optical beam [26,27]. This direct free-space coupling is of importance because it is robust and requires less rigorous experimental condition than the evanescent couplers mentioned above.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As the time reversal process, the WGMs of microcavity can also be excited by the focused light in free space, which is known as free space coupling [12,13]. The free space coupling does not require precise position control and the coupling efficiency can be higher than 30% [14][15][16][17]. This method has been successfully applied in biosensors and laser pumping [9,17].…”
Section: Introductionmentioning
confidence: 99%
“…Ray dynamically, these three different structures are disjoint in SOS. However, in wave optics, dynamic tunneling between the regular orbits and neighboring chaotic orbits can take place (25,(29)(30)(31)(43)(44)(45)(46), where the latter eventually refract out from the cavity following an unstable manifolds channel (green curves) (44) when crossing the total internal reflection critical line (red dashed line). It is worth noting that the chaotic motion along the unstable manifolds channel is a momentum transformation process.…”
Section: A Ray Dynamics Analysis Of Deformed Microresonatormentioning
confidence: 99%